Cost-benefit analysis of an employee assistance program for a geographically dispersed workforce in South Australia. (2nd January 2020) - Elson, Tony D.; Heinrich, Susan R.; Richards, Jane F.; Wirawan, Rama Y.; Shepard, Donald S.
Abstract: The South Australia Department for Education employs approximately 30, 000 people (40.2% outside the major city, Adelaide). This study conducted a cost-benefit analysis of its employee assistance program from the Department's perspective, focusing on remoteness. The employee assistance program utilization rate outside the major city was 13% below that in the major city. Based on improved absenteeism and presenteeism, measured fiscal benefits per user (1, 365.79 Australian dollars [AUD] or 1, 021.48 US dollars [USD]) were 3.34 times the costs (409.27 AUD or 306.09 USD), indicating a highly favorable return. Our sensitivity analysis found that if the increase in student lifetime earnings, worth about 76, 000 AUD (57, 000 USD) yearly, had been included, it would have increased the total benefits by 5.3% and raised the benefit-cost ratio to 3.51. Although telephone sessions were available, the average number of sessions per participant was 49% higher for the in-person only modality (2.82) compared to the telephone-only modality (1.89). This apparent preference for in-person sessions indicates a challenge for regional and remote areas, where access is difficult. The study recommends proactive measures to increase utilization outside its major city.